Damp housing, mould growth, and symptomatic health state. Issue 6689 (24th June 1989) - Platt, S. D.; Martin, C. J.; Hunt, S. M.; Lewis, C. W.
Abstract : OBJECTIVE--To examine the relation between damp and mould growth and symptomatic ill health. DESIGN--Cross-sectional study of random sample of households containing children; separate and independent assessments of housing conditions (by surveyor) and health (structured interview by trained researcher). SETTING--Subjects' homes (in selected areas of public housing in Glasgow, Edinburgh, and London). SUBJECTS--Adult respondents (94% women) and 1169 children living in 597 households. END POINTS--Specific health symptoms and general evaluation of health among respondents and children over two weeks before interview; and score on general health questionnaire (only respondents). MEASUREMENTS AND MAIN RESULTS--Damp was found in 184 (30.8%) dwellings and actual mould growth in 274 (45.9%). Adult respondents living in damp and mouldy dwellings were likely to report more symptoms overall, including nausea and vomiting, blocked nose, breathlessness, backache, fainting, and bad nerves, than respondents in dry dwellings. Children living in damp and mouldy dwellings had a greater prevalence of respiratory symptoms (wheeze, sore throat, runny nose) and headaches and fever compared with those living in dry dwellings. The mean number of symptoms was higher in damp and mouldy houses and positively associated with increasing severity of dampness and mould (dose response relation). All these differences persisted after controlling for possible confounding factors such as household income, cigarette smoking, unemployment, and overcrowding. Other possible sources of bias that might invalidate the assumption of a causal link between housing conditions and ill health--namely, investigator bias, respondent bias, and selection bias--were also considered and ruled out. CONCLUSION--Damp and mouldy living conditions have an adverse effect on symptomatic health, particularly among children.